2023
DOI: 10.1002/etc.5568
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity of 6PPD‐Quinone to Early Life Stage Juvenile Chinook (Oncorhynchus tshawytscha) and Coho (Oncorhynchus kisutch) Salmon

Abstract: The breakdown product of the rubber tire antioxidant N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine-quinone (6PPD)-6-PPD-quinone has been strongly implicated in toxic injury and death in coho salmon (Oncorhynchus kisutch) in urban waterways. Whereas recent studies have reported a wide range of sensitivity to 6PPD-quinone in several fish species, little is known about the risks to Chinook salmon (Oncorhynchus tshawytscha), the primary prey of endangered Southern Resident killer whales (Orcinus orca) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 36 publications
1
32
1
Order By: Relevance
“…Our results confirm the high sensitivity of juvenile coho salmon to 6PPDQ as well as the substantially greater tolerance to acute toxicity in closely related species. ,, The relative order of sensitivity seen here (coho > Chinook > sockeye) is also consistent with exposure to undiluted urban stormwater runoff . Interestingly, in that study, undiluted stormwater elicited low-level mortality (∼13%) in young of the year Chinook salmon with the common suite of URMS symptoms.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Our results confirm the high sensitivity of juvenile coho salmon to 6PPDQ as well as the substantially greater tolerance to acute toxicity in closely related species. ,, The relative order of sensitivity seen here (coho > Chinook > sockeye) is also consistent with exposure to undiluted urban stormwater runoff . Interestingly, in that study, undiluted stormwater elicited low-level mortality (∼13%) in young of the year Chinook salmon with the common suite of URMS symptoms.…”
Section: Resultssupporting
confidence: 84%
“…Interestingly, in that study, undiluted stormwater elicited low-level mortality (∼13%) in young of the year Chinook salmon with the common suite of URMS symptoms. 6PPDQ concentrations from that stormwater source have not been reported to exceed 1 μg/L, well below lethal concentrations reported for both younger swim-up stage Chinook and older juveniles here. Therefore, URMS symptoms and mortality observed in Chinook salmon exposed to runoff was unlikely due solely to 6PPDQ, but rather a result of multiple contaminants in stormwater, which include other PPDs and PPDQs with unknown toxicological profiles.…”
Section: Resultscontrasting
confidence: 41%
See 1 more Smart Citation
“…We also calculated the acute risk quotient (RQ) using the LC 50 for adult coho salmon of 95 ng L –1 . We note that an LC 50 of 41 ng L –1 was recently reported by Lo et al for juvenile Coho salmon, using this value would increase all of the reported RQs by 2.3 times. We used the RQ to calculate an average (RQ av ) based on the MEC.…”
Section: Methodsmentioning
confidence: 93%
“…For coho salmon, the primary toxicant in road runoff was recently discovered to be the compound 6PPD-quinone ( N -(1,3-dimethylbutyl)- N ′-phenyl- p -phenylenediamine-quinone), which is produced as a transformation product when atmospheric ozone reacts with 6PPD, an antiozonant tire additive . 6PPD-quinone has been found at toxicologically relevant levels in many urban streams across North America, and in road dust in Japan, and further research has shown that a number of other salmonid species are impacted at environmentally relevant concentrations of 6PPD-quinone. 6PPD-quinone toxicity is an area of evolving research, with results indicating that juvenile salmon are also very sensitive to 6PPD-quinone exposure, that toxicity is not consistent among aquatic organisms, and that the modes of toxicity are not fully understood …”
Section: Introductionmentioning
confidence: 99%